The inclination of psychological disorder of post sectio caesarean based on characteristic - Ni Wayan Dewi Purwanti; Ni Komang Erny Astiti; I G A A Novya Dewi; I Nyoman Hariyasa Sanjaya; I Nyoman Wirata; G. A Eka Utarini (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Psychological problems in postpartum mothers, both vaginal postpartum and post SC, can have a negative impact on the cognitive development of babies and can reduce maternal and infant bonding. Post SC have a risk of postpartum depression four times greater than mothers with vaginal deliveries. However, previous studies looked at postpartum mothers in general, not specifically in post-SC who had a higher risk. Research related to early detection of the risk of post-SC psychological disorders is quite limited.  The prevalence of mothers with postpartum depression symptoms in Denpasar in 2019 was 25.4%. Early detection can be done using the Edinburgh Postpartum Depression Scale (EPDS).Objectives: The aims of this research to identify the psychology of post SC mothers based on characteristics including age, race/ethnicity, last education, income, pregnancy status, parity, living with a nuclear or large family, lactation problems, and type of SC in the Dr.dr. I Nyoman Hariyasa Sanjaya,SpOG(K)-KFM.MARS 2022.Methods: Descriptive research design with a cross-sectional subject approach model. The sample of this research is 34 samples with the Consecutive Sampling technique. Types of primary data taken by EPDS and characteristic questionnaire. This study uses quantitative descriptive univariate analysis.Results: The prevalence of Post SC which indicates a psychological disorder is 44.12%. Post SC which indicates more psychological disorders are mothers with a productive age range of 20-35 years by 26.47%, Asian race 41.18%, higher education level which is 38.24%, very high revenue 38.24%, desired pregnancies status 35.29%, 29.41% multiparas, 23.53% mothers living with large families, 38.24% experiencing lactation problems, and 26,47% elective SC types.Conclusions: This study found that 44.12% of Post SC indicated experiencing psychological disorders, the majority were Post SC at the age of 20-35 years, Asian race, good education, very high revenue, desired pregnancy status, multipara, mothers living with large families, mothers with lactation problems, and elective cesarean section. The environment and health workers can conduct screening as early as possible so that the impact of this psychological disorder can be prevented.